Analisis Perubahan Tutupan Lahan Dan Arah Perkembangan Lahan Terbangun di Kecamatan Katobu - Leni Marlina; La Ode Hadini; L.M Iradat Salihin; Fitriani Fitriani (Universitas Halu Oleo, 2024)
Land cover undergoes changes every year. Such development might be uncontrolled, making it crucial to monitor changes in land cover. Monitoring land cover changes can be conducted using satellite imagery, especially Landsat images. This study was conducted in the Katobu District, Muna Regenvy, and aimed to: (1) identify changes in land cover from 2017-2022 in the Katobu Subdistrict, Muna District; (2) analyze the direction of built land development from 2017-2022; (3) understand the factors influencing the direction of built land development. The data used in this study include the type of land cover from Landsat images, sample coordinate points from field surveys, and data on factors affecting the direction of built land development obtained from interviews. The data analysis methods used are overlay and quantitative descriptive. The research results include: (1) the most significant land cover change from 2017-2022 was the transformation from shrub land to built land, with a change of 27,86 hectares or 2,84%; (2) the direction of built land development in the Katobu Subdistrict from 2017-2022 tends to head towards the Batalaiworu Subdistrict; (3) the influencing factors are non-physical factors such as population growth/total population and city activities.